Chaos control via feeding switching in an omnivory system. (December 2015) - Chattopadhyay, Joydev; Pal, Nikhil; Samanta, Sudip; Venturino, Ezio; Khan, Q.J.A.
Abstract: Tanabe and Namba ( Ecology, 86, 3411–3414) studied a three species Lotka–Volterra model with omnivory and explored that omnivory can create chaos. It is well documented that predator switching is a similar biological phenomenon to omnivory and likely to occur simultaneously. In the present paper, the tri-trophic Lotka–Volterra food web model with omnivory and predator switching is re-investigated. We observe that if we incorporate predator switching in the system and the intensity of predator switching increases above a threshold value, then the system will be stable from chaotic dynamics. To study the global dynamics of the system extensive numerical simulations are performed. Our analytical and numerical results suggest that predator switching mechanism enhances the stability and the persistence of a food chain system.